Impact of parent-child separation on children's social-emotional development: a cross-sectional study of left-behind children in poor rural areas of China - Huifeng Shi; Yuanyuan Wang; Mengshi Li; Chang Tan; Chunxia Zhao; Xiaona Huang; Yan Dou; Xiaoqian Duan; Yufeng Du; Tianchen Wu; Xiaoli Wang; Jingxu Zhang (BMC, 2021)
Abstract Background Parent-child separation is a considerable adversity for left-behind children (LBC), but there is little evidence on the association between detailed characteristics of parent-child separation and social-emotional development among LBC. This study examined the characteristics of parent-child separation and its impacts on developmental delay among under-3 LBC in poor rural China. Methods We used data from 811 LBC surveyed in five poor counties in rural China in 2018. Detailed characteristics of their parental migration were recalled by their primary caregivers in face-to-face interviews. The children's social-emotional development was measured by using the Ages and Stages Questionnaire: Social-Emotional. Logistic regression was employed to examine the association of detailed characteristics of parent-child separation with early social-emotional problems after adjusting for the children's and primary caregivers' sociodemographic characteristics. Results 287 (35.4%) children were left behind by fathers and cared for by mothers (FM-MC), while 524 (64.6%) were left behind by both parents and cared for by grandparents (PM-GC). The rate of social-emotional problems among LBC was 36.8% (PM-GC vs FM-MC: 40.6% vs 29.5%; aOR 1.51, 95% CI: 1.06 to 2.16). For paternal migration, the medians of the child's age at the first migration and average duration per migration were 3 months (IQR: 1 to 9 months) and 4.48 months (IQR: 2.38 to 7.54 months), respectively. For maternal migration, the corresponding values were 9 months (IQR: 6 to 13 months) and 4.65 months (IQR: 2.71 to 7.62 months), respectively. On average, LBC had been separated from fathers for 72% of their life due to paternal migration and from mothers for 52% of their life due to maternal migration. No significant association was found between the detailed characteristics of paternal migration and social-emotional development among LBC, while social-emotional problems among LBC were significantly associated with the proportion of cumulative duration of maternal migration in the child's lifetime (aOR 2.83; 95% CI: 1.13 to 7.10). Conclusions LBC under 3 years had a high risk of social-emotional problems in poor rural China. Cumulative exposure to maternal migration may be detrimental to LBC's early social-emotional development. Programs are necessary to support these children as well as their families.